2021
DOI: 10.1097/ju.0000000000001943
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Disease after Bacillus Calmette-Guérin Therapy: Refining Patient Selection for Neoadjuvant Chemotherapy before Radical Cystectomy

Abstract: Purpose:Data from the pre-neoadjuvant chemotherapy (NAC) era suggests patients who progress on bacillus Calmette-Guérin (BCG) to muscle-invasive bladder cancer (P-MIBC) exhibit worse outcomes compared to de novo MIBC (D-MIBC). Herein, we investigate whether P-MIBC is an independent poor risk factor in the setting of contemporary NAC use.Materials and Methods:A review of patients who underwent radical cystectomy (RC) for cT2-3 MIBC from 2005 to 2018 was performed. Patients were stratified into high risk (lympho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Patients with secMIBC experienced the worst survival outcomes (RFS, CSS, and OS) and secMIBC was an independent predictor of worse CSS and OS. Previous studies reported conflicting survival outcomes for secMIBC compared to primMIBC [10] , [11] , [12] , [13] . The most recent meta-analysis, which included 16 studies with a total of 5270 patients, revealed no differences in 5- and 10-yr CSS and OS between these two groups [12] .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Patients with secMIBC experienced the worst survival outcomes (RFS, CSS, and OS) and secMIBC was an independent predictor of worse CSS and OS. Previous studies reported conflicting survival outcomes for secMIBC compared to primMIBC [10] , [11] , [12] , [13] . The most recent meta-analysis, which included 16 studies with a total of 5270 patients, revealed no differences in 5- and 10-yr CSS and OS between these two groups [12] .…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies showed that patients who underwent RC for recurrent HR-NMIBC had worse oncological outcomes than those with primary HR-NMIBC [7] , [8] , [9] . By contrast, data comparing oncological outcomes for patients with primary and secondary MIBC are conflicting [10] , [11] , [12] , [13] . There are no conclusive data regarding the comparative prognosis of RC for primary HR-NMIBC, recurrent HR-NMIBC, secondary MIBC, and primary MIBC.…”
Section: Introductionmentioning
confidence: 99%
“…Hensley et al (page 1258) from Houston, Texas explored in a comparative study whether neoadjuvant chemotherapy (NAC) impacts these findings. 5 In a study of 801 patients, the authors again found that progression on BCG portended a worse prognosis than cystectomy in de novo patients in the absence of NAC. In the subgroup of patients with progression who were treated with NAC, the adverse implications were abrogated.…”
Section: Progression Of Disease After Bacillus Calmette-guérin Therapymentioning
confidence: 96%
“…While guidelines support the role of NAC before radical cystectomy for MIBC, there remains a role for risk-stratified NAC patient selection. Clinicopathologic risk factors have been implemented in predicting response to cisplatin-based NAC [77,78], but efforts are underway to profile tissue-based biomarkers for this purpose. The Southwest Oncology Group (SWOG) 1314 trial prospectively profiled the ability of the COXEN tissue-based genetic classifier to predict complete pathologic response to cisplatin-based NAC (Table 2) [79].…”
Section: Unmet Needs In Biomarker Developmentmentioning
confidence: 99%